Adopsi teknologi sebagai alternatif untuk peningkatan daya saing UMKM Surakarta pasca Covid-19 - Wibowo, Frendy; Agra, Belligo; Husain, Fida (Nur Science Institute, 2021)
The rapid development of technology in the last few decades has impacted the business world. Information technology is one of the best examples of that rapid development. Large companies aware of the importance of information technology seek to increase its use to increase competitiveness in the market. In contrast to the conditions in the SME sector, it has not significantly comprehensively adopted information technology to increase competitiveness in the industry. This study uses a qualitative method. The respondents of this study were MSMEs who were randomly selected using snowball sampling by previous informants from various sectors regardless of the size of their business. Informants from the MSMEs are business owners with different educational backgrounds and experiences. We will only look at the status of MSMEs in deciding whether or not they are ready to use information technology to increase competitiveness in the industry. We found that four main factors become the basic considerations for SMEs in Surakarta to use or not to use information technology to increase competitiveness in the industry